Investigation of the relationship between virulence factors and antibiotic resistance of Enterococci isolates - Say Coskun, Umut Safiye (Cellular and Molecular Biology, 2019)
The aim of this study was to determine the relationship between aggregation factor (asa1), enterococcal surface protein (esp), cytolysin (cyl), gelatinase (gelE), hyaluronidase (hyl) virulence factors and antibiotic resistance in Enterococci. VITEK 2 ID system was used to identify the isolates and determine their antibiotic susceptibility. Virulence genes were investigated by polymerase chain reaction. Of the 93 isolates, 62 (66 %) were Enterococcus faecium, 31 (44 %) were Enterococcus faecalis (E. faecialis ). E. faecium isolates were more resistant to ampicillin, ciprofloxacin, linezolid, teicoplanin and vancomycin than E. faecalis. High-level gentamycin rate were higher in E. faecium than E. faecalis (p <0.05). The most prevalant virulence genes were esp (60.9 %) and asa1 (25 %) followed by gelE (22.8 %), cyl (16.3 %) and hyl (8.7 %). Asa1, cyl, gelE genes positivity were higer in E. faecalis than E. faecium. Hyl positivity was higher in E. faecalis than E. faecium isolates. Ampicillin resistance was higher in gelE positive E. faecalis than gelE negative E. faecalis (p <0.05). Ciprofloxacin resistance was higher in gelE negative E. faecalis than gelE positive E. faecalis (p <0.05). Asa, cyl, hyl, gelE positive E. faecium isolates were more susceptible to teicoplanin than the isolates that did not have these genes (p <0.05). Cyl, asa, gelE positive E. faecalis isolates were more susceptible to vancomycin than cyl, asa, gelE negative E. faecalis isoates (p <0.05). Hyl positive E. faecium isolates were more susceptible to vancomycin than hyl negative E. faecium isolates (p <0.05). E. faecalis isolates that have virulence genes were more susceptible to vancomycin (p <0.05). The resistance to antibiotics in E. faecalis should be a concern for the treatment of infectious disease.